2021
DOI: 10.2147/ndt.s307662
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the Clinically Useful Depression Outcome Scale for Patients with Major Depressive Disorder

Abstract: Objective: This study aimed to evaluate the psychometric properties of the Chinese version of the Clinically Useful Depression Outcome Scale (CUDOS). Methods: One hundred ninety patients with major depressive disorder (MDD) according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria were recruited to the study. The English version of the CUDOS was translated into Chinese using a forward and backward translation method, which was according to the guidelines of adaptation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…However, the proportion of raw variance data, high disattenuated correlations and person correlations suggested that the Chinese version of CUDOS is a unidimensional contruct scale, which was consistent with previous studies by CTT [11,14]. Hence results in the current study supported a unidimensional construct the Chinese version of CUDOS.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, the proportion of raw variance data, high disattenuated correlations and person correlations suggested that the Chinese version of CUDOS is a unidimensional contruct scale, which was consistent with previous studies by CTT [11,14]. Hence results in the current study supported a unidimensional construct the Chinese version of CUDOS.…”
Section: Discussionsupporting
confidence: 91%
“…Although the Chinese version of CUDOS has been validated in Chinese patients with MDD using CTT [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations